2004
DOI: 10.1016/j.jtcvs.2003.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Arterial switch with full-flow cardiopulmonary bypass and limited circulatory arrest: Neurodevelopmental outcome

Abstract: With the perioperative strategies used, not all survivors can be considered (neurodevelopmentally) normal at late follow-up, although the risk of important impairment is low. Perioperative events might have long-term prognostic value. On the basis of this study and published data regarding other strategies, continued application of full-flow cardiopulmonary bypass is justified, with the proviso that further investigation is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(66 citation statements)
references
References 22 publications
7
54
0
5
Order By: Relevance
“…Our findings are concordant with previous publications demonstrating a high lifetime prevalence of ADHD, with inattention and hyperactivity, in children with congenital heart disease. 24-26 Given the high rates of ADHD associated with d-TGA, 27-29 the effectiveness of stimulants in ADHD, 30,31 and the reported tolerability of these medications in youth with complex heart disease, 28 primary care clinicians and cardiologists should consider psychotropic medication as a treatment option.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are concordant with previous publications demonstrating a high lifetime prevalence of ADHD, with inattention and hyperactivity, in children with congenital heart disease. 24-26 Given the high rates of ADHD associated with d-TGA, 27-29 the effectiveness of stimulants in ADHD, 30,31 and the reported tolerability of these medications in youth with complex heart disease, 28 primary care clinicians and cardiologists should consider psychotropic medication as a treatment option.…”
Section: Discussionmentioning
confidence: 99%
“…65 A variety of pre- and post-operative factors are thought to increase the risk of these problems including the type of cardiac lesion, 66 preoperative hypoxia, 64 low pH, 67 age at surgery, 65 palliative versus corrective operative procedure, 62 deep hypothermic cardiac arrest, 68 and length of cardiac intensive care unit stay. 65 …”
Section: Introductionmentioning
confidence: 99%
“…Hövels-Gürich et al (42) and Karl et al (19) showed an increased risk of parent-reported psychosocial maladjustment in children and adolescents with d -TGA. In the BCAS, 16-year-olds with d -TGA were more likely than controls (35 versus 20%) to meet criteria for a lifetime psychiatric diagnosis, as evaluated by the Schedule for Affective Disorders and Schizophrenia for School-aged Children (K-SADS) (45).…”
Section: Adolescents With D-tga: Cognitive and Psychiatric Outcomesmentioning
confidence: 97%
“…Nevertheless, deficits are often apparent in specific neurocognitive areas. Speech and motor impairments were reported in both European (17, 18) and North-American studies (13, 19). Bellinger et al (12, 13) reported below age-expected scores for 4- and 8-year-old children in visual–spatial skills, academic achievement, working memory, hypothesis generation, sustained attention, and higher order language skills.…”
Section: Neuropsychological Outcomes In Children With D-tgamentioning
confidence: 99%